2002
DOI: 10.1002/ajim.10032
|View full text |Cite
|
Sign up to set email alerts
|

Mica dust as a cause of severe pneumoconiosis

Abstract: This report indicates that mica exposure may result in mica pneumoconiosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 8 publications
0
10
0
Order By: Relevance
“…Quartz is known to cause silicosis (another pneumoconiosis), although only one worker in this cohort died from silicosis. Vermiculite belongs to the mica family; mica has previously been linked with pneumoconiosis (Skulberg et al 1985; Venter et al 2004; Zinman et al 2002). …”
Section: Discussionmentioning
confidence: 99%
“…Quartz is known to cause silicosis (another pneumoconiosis), although only one worker in this cohort died from silicosis. Vermiculite belongs to the mica family; mica has previously been linked with pneumoconiosis (Skulberg et al 1985; Venter et al 2004; Zinman et al 2002). …”
Section: Discussionmentioning
confidence: 99%
“…5 6 22 23 From these reports it is clear that pure mica can cause pneumoconiosis, even with short duration of exposures. 6 The pneumoconiosis cases here described showed a mean of 17 years of exposure and 23 years of latency time. One of the cases had an exposure time as low as 1.4 years.…”
Section: Discussionmentioning
confidence: 80%
“…2 However, several case reports presented with careful pathological and mineralogical analysis leave little doubt that mica with low quartz content can be associated with the development of disabling forms of pneumoconiosis. [4][5][6] Interestingly, sericite was thought to be one of the main causes of lung disease in underground coal workers, and the object of a historical scientific dispute that led to the broadening of acceptance criteria for compensation of disabled coal miners. 7 Previous cytotoxic studies, with dust collected in British collieries, showed an enhanced cytotoxic effect for the noncoal mineral content of the samples, mainly kaolin and mica.…”
mentioning
confidence: 99%
“…Mica dust can cause pneumoconiosis (Short and Petsonk 1996; Zinman et al 2002), characterized by nodular and reticular infiltrates especially in the lower lung fields. However, pneumoconiosis due to mica appears to be rare (Morgan 1995).…”
Section: Discussionmentioning
confidence: 99%